Tkánové helmintózy - Kolárová, Libuse (Klinicka mikrobiologie a infekcni lekarstvi, 2006)
Helminthic infections affecting host organs/tissues belong to the most important parasitic infections. In the Czech Republic, an increase in the travelers to and immigrants from endemic countries has been noted. Except for larval toxocarosis, however, the total number of patients with schistosomiasis, hydatid disease, cysticercosis and filariases does not exceed 15 cases per year till present. It remains to be solved whether this situation reflects manners of a Czech tourist in endemic areas or the diseases are neglected during routine practice. The presented paper, therefore, focuses on some diagnostically important features accompanying helminthic infections. And, clinical symptoms and signs of the infections are analysed in relation to the patient history and laboratory findings.
Keywords: Helminthiasis; Humans; Česká republika; lidé; cestování; helmintóza; Travel; Czech Republic